Fatores de risco para a cárie dentária em pacientes com deficiências do desenvolvimento - Ana Paula Vasques Sales Braúna (2016)
The aim of the present study was to investigate risk factors for dental caries in children with developmental disabilities who were treated at a reference service for Patients with Special Needs, Belo Horizonte, MG, Brazil. This is a retrospective cohort that evaluated 401 dental charts of individuals without dental caries or dental fillings in his/her first dental appointment. Dependent variable was the occurrence of a new dental caries lesion or restoration. The time to occurrence of a new carious lesion or restoration was measured in months. Gender, age, International Code of Diseases (ICD), mother´s education, sugar consumption, use of toothpaste with fluoride, oral hygiene, mouth breathing, reports of xerostomia, gingival status, use of psychotropic drugs, use of asthma drugs, history of asthma were covariates. Cox proportional hazards regression model was used to estimate the raw and adjusted hazard ratios with their respective 95% confidence interval. The average time that individuals remained free of dental caries/restoration was equal to 107.46 months (95% CI 95.41 to 119.51), with a median of 94 months. For each one point increase in the scale of sucrose consumption, increases the risk of caries 1.07 (95% CI 1.01 to 1.15). The sucrose consumption was the only risk factor for dental caries in this group of individuals with developmental disabilities.